THEORETICAL-METHODICAL ASPECTS CONCERNING THE ORGANISATION OF SCHOOL PHYSICAL EDUCATION AT THE LEVEL OF PRIMARY SCHOOL (University Arena, 2025)
Background. In the last years, both in Romania, as well as in other European countries, a series of changes were operated in the training process, including at the subject of Physical Education of pupils in the primary school, when actually the foundation of their multilateral development is formed. In order to achieve the basic objectives of physical education at the level of primary school, here are some suggestions of modern methodologies to change the training process of the above-mentioned subject. Therefore, in this paper there are described the basic requirements as related to the training process of pupils in the primary school at the subject of Physical Education, as well as the ways to optimize this, aiming to successfully meet the basic goals at the given subject and ensuring the multilateral-scoped training of the graduate of primary school.
Keywords: physical education; pupils; primary school; physical training; physical development